ZnMgSe:Cr²⁺ single crystal: a novel material for active elements of tunable IR region lasers (rapid communication) - Zagoruiko, Yu.A.; Kovalenko, N.O.; Fedorenko, O.A.; Khristyan, V.A. (Functional Materials, 2008)
Obtained is a new thermostable material for active elements of tunable IR-lasers - Zn₁₋ₓMgₓSe:Cr²⁺, single crystals. The position of the absorption band of Cr²⁺ ions in wurtzite-type Zn₀.₇₉Mg₀.₂₁Se matrix is established.